2023
DOI: 10.1002/anie.202308413
|View full text |Cite
|
Sign up to set email alerts
|

In situ Engineering of Tumor‐Associated Macrophages via a Nanodrug‐Delivering‐Drug (β‐Elemene@Stanene) Strategy for Enhanced Cancer Chemo‐Immunotherapy

Abstract: Tumor‐associated macrophages (TAMs) play a critical role in the immunosuppressive solid tumor microenvironment (TME), yet in situ engineering of TAMs for enhanced tumor immunotherapy remains a significant challenge in translational immuno‐oncology. Here, we report an innovative nanodrug‐delivering‐drug (STNSP@ELE) strategy that leverages two‐dimensional (2D) stanene‐based nanosheets (STNSP) and β‐Elemene (ELE), a small‐molecule anticancer drug, to overcome TAM‐mediated immunosuppression and improve chemo‐immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Monocytes release large amounts of inflammatory mediators, creating an inflammatory environment that promotes tumor growth and creates a fertile ecological environment for cancer development. 44 Meanwhile, the expression of regulatory T cells was higher in the high-risk group, and these cells are capable of generating an immunosuppressive microenvironment that hinders the CD8+ T cell-mediated eradication of tumor cells, which in turn promotes tumorigenesis progression. 45 In recent years, considerable breakthroughs have been made in cancer treatment using monoclonal antibodies against immune checkpoint molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes release large amounts of inflammatory mediators, creating an inflammatory environment that promotes tumor growth and creates a fertile ecological environment for cancer development. 44 Meanwhile, the expression of regulatory T cells was higher in the high-risk group, and these cells are capable of generating an immunosuppressive microenvironment that hinders the CD8+ T cell-mediated eradication of tumor cells, which in turn promotes tumorigenesis progression. 45 In recent years, considerable breakthroughs have been made in cancer treatment using monoclonal antibodies against immune checkpoint molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltrated immune cells are directly related to the prognosis of patients with tumors. Monocytes and macrophages release large amounts of inflammatory mediators that promote tumor growth and reduce anti-tumor immunity [ 41 ]. Monocytes and macrophages were substantially enriched in the high-risk group, with a strong positive correlation between RS and these cells.…”
Section: Discussionmentioning
confidence: 99%
“…2). 28 This study illustrated that both STNSP and ELE can reprogram tumor-supportive macrophages into a tumor-suppressive phenotype through an intracellular reactive oxygen species (ROS)-activating manner. The results from a melanoma mouse model indicated that STNSP@ELE treatment successfully reprogrammed the TME by significantly elevating the ratio of M1/M2-like TAMs and increasing the populations of CD4 + and CD8 + T-lymphocytes and dendritic cells, leading to a robust anti-tumor immunostimulatory response.…”
Section: Macrophage-modulating Strategiesmentioning
confidence: 95%